On-field methodological approach to monitor the menstrual cycle and hormonal phases in elite female athletes - Dupuit, M.; Meignié, A.; Chassard, T.; Blanquet, L.; LeHeran, J.; Delaunay, T.; Bernardeau, E.; Toussaint, J.-F.; Duclos, M.; Antero, J. (International Journal of Sports Physiology and Performance, 2023)
Objectives: Currently, there are no guidelines for implementing the monitoring of menstrual status, including the natural menstrual cycle (NC) or oral contraception (OC), in a sport setting. We aimed to provide a feasible, on-field methodological approach for monitoring NC and OC in female athletes.